Accessibility Barriers, Conflicts, and Repairs: Understanding the Experience of Professionals with Disabilities in Hybrid Meetings - Alharbi, Rahaf; Tang, John; Henderson, Karl (CHI 2023, 2023)
Workplaces around the globe are beginning to rapidly adopt hybrid meetings to conduct, plan, and organize their work. While previous literature explores the benefits and drawbacks of hybrid meetings, the experiences of professionals with disabilities are largely missing. With an orientation towards an accessible future of work, we interviewed 21 professionals with disabilities to unpack the accessibility barriers, opportunities, and conflicts of hybrid meetings. We highlight the creative ways professionals with disabilities developed workarounds and repairs to these accessibility tensions. Our paper expands the understanding of accessibility in hybrid meetings by identifying how the visibility of access labor may be affected by being in the room together with other colleagues or joining remotely. We also observed how hybrid configurations can require navigating accessibility conflicts specific to the location site of each participant. Building from our analysis, we offer practical suggestions and design directions to make hybrid meetings accessible.